Faktor yang berhubungan dengan Catatan Keperawatan Dokumen Rekam Medis Rawat Inap di Rumah Sakit H. Adam Malik Medan - Achmad Sobari; Mappeaty Nyorong; Nuraini Nuraini (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Nursing records are one of the most important aspects of the role of health care providers because they are evidence of the implementation of nursing care. Nursing documentation confirms that the legal and ethical responsibilities of nurses to patients have been fulfilled, and patients receive quality nursing care. Quality medical records are related to the completeness of medical record entries, accuracy, accuracy of medical record records, timeliness and fulfillment of legal aspects. The purpose of this study was to determine factors related to nursing records of inpatient medical records at H. Adam Malik Hospital Medan This study uses an analytical survey method with a cross sectional approach. The population in this study were all 50 inpatient nurses and 50 samples were taken using a total sampling technique. Data analysis used univariate, bivariate and multivariate analysis with data analysis using logistic regression test. The results of the chi-square test analysis show that the p-value of each variable includes workload, p-value = 0.022, performance p-value = 0.018 and supervision p-value = 0.046. The conclusion of this study is that there is a relationship between workload, performance and supervision with inpatient medical records. It is expected to carry out regular and periodic supervision of each implementing nurse in the inpatient room, in this case the head of the room needs to plan direct and indirect supervision activities on a regular basis and is also involved in the implementation of nursing records